Report of the Working Group on Agricultural Education on Vocational Agricultural Education - Planning Commission (Planning Commission, 1968)
The Working Group on Vocational Agricultural Education, convened under India’s Fourth Plan proposals, emphasized the need for practical, hands-on training for rural youth to promote sustainable farming practices. Targeting students aged 14 and above, courses were recommended to be located in agricultural areas and conducted primarily on home farms, supported by experimental learning and instructional materials in regional languages. Qualified teachers with agricultural degrees and field experience were deemed essential, and integration with existing curricula was encouraged. The report recommended centralized coordination by the Ministry of Agriculture, state-level oversight, phased implementation beginning with 25 centres, and immediate financial provision to ensure pilot projects effectively enhance rural livelihoods through agricultural education.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Vocational Agricultural Education; Junior Agricultural Schools; Practical Training; Rural Students; Home Farm Instruction; Teacher Qualifications; Curriculum Integration; Agricultural Colleges; Ministry of Agriculture; State Boards; Implementation Plan; Pilot Projects